Twisting light without spin: chirality-sensitive forces from linear polarization - Giuseppina Simone (JPhys Photonics)
Optical lateral forces provide a powerful tool for probing spin-dependent light–matter interactions that extend beyond conventional radiation pressure or gradient effects. While chirality-dependent forces have traditional required circularly polarized light, here, it is demonstrated their emergence under linearly polarized illumination through photonic structure-induced helicity. Using a transversely electric-polarized wave interacting with a multilayer system of silver-coated silicon antennae, evanescent fields where structural inhomogeneities support magnetic dipole resonances have been generated. The inhomogeneities create localized magnetic moments that enable spin–momentum locking in the near field, producing chirality-dependent lateral forces, independent of the incident beam’s helicity. Through detailed analysis of the reflected beam, it has been verified the coexistence of transverse spin and longitudinal canonical momentum components while characterizing the evanescent wave’s helicity. The experiments reveal helicity-dependent scattering from magnetic dipoles and demonstrate opposite-direction lateral displacement of chiral enantiomers. The findings establish that structured photonic systems can generate optical chirality without circular polarization, opening new possibilities for chirality-selective optical manipulation, nanoscale force sensing, and fundamental studies of spin–orbit photonic phenomena.